Empowering Organic Farmer through Innovation in Indonesia: A Participatory Guarantee System Model - Vanda NINGRUM; Triyanti ANUGRAHINI (Communications of International Proceedings, 2020)
Many studies define the Participatory Guarantee System (PGS) as a social innovation to help small-scale organic farmers gain access to organic guarantee and promote social inclusion. This study explores farmer empowerment in PGS Pacet in Claket Village, East Java Province, Indonesia. Data obtained by Interviews with 15 farmers and were analyzed with empowerment theory. This study found that the organic farming and PGS model able to empower collective and individual farmers. In collective, PGS facilitates groups to increase their capacity to maintained business sustainability, expand the market network, and improve their group’s income. For individuals, the PGS could improve farmers' agriculture and social skills, increase their self-esteem, and boost household income. Thus, the PGS model also provides access for farmers to build better relationships with consumers and communities in the village. Based on these findings, the PGS model is essential for organic farming communities, especially for smallholders.
Keywords: Empowerment; Participatory Guarantee System (PGS); Organic Farmers.